If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1 = 13x + -71 Reorder the terms: -1 + 6x = 13x + -71 Reorder the terms: -1 + 6x = -71 + 13x Solving -1 + 6x = -71 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -1 + 6x + -13x = -71 + 13x + -13x Combine like terms: 6x + -13x = -7x -1 + -7x = -71 + 13x + -13x Combine like terms: 13x + -13x = 0 -1 + -7x = -71 + 0 -1 + -7x = -71 Add '1' to each side of the equation. -1 + 1 + -7x = -71 + 1 Combine like terms: -1 + 1 = 0 0 + -7x = -71 + 1 -7x = -71 + 1 Combine like terms: -71 + 1 = -70 -7x = -70 Divide each side by '-7'. x = 10 Simplifying x = 10
| z-5=19 | | -4n+2-5=-3 | | -4=-(2+7a)-10a | | 55=5e | | x+23=-35 | | 6(5x+1)=2x-8x | | 378=18xz | | 71-6x=12x+15 | | 3(-2a+2)=9a-10 | | 13-10x=37-24x | | 3(-2+2)=9a-10 | | 2x+3x-12=4x-25 | | -127-8x=7x+23 | | 10+p=23 | | 3=10v-(-4v+1) | | k-13=18 | | 4x+6=-49-7x | | 3=10v-(4v+1) | | 75-3x=2x+15 | | 9+x=16 | | -1=-(3-8k)-k | | -8=-7m-(-3m+2) | | 6a-3(6-4a)=-6 | | 5x+78=11x+12 | | 65t=390 | | y-8=605 | | c-4=5 | | 18=b+9 | | 3(8n+2)+2=2-9n | | 5m-(-45k)+10m-10k= | | x+68=110 | | 3x^2-2=5x |